Research Regarding Observation of Spatial Segregation in Ankara-Altindag Hill Squatter Region - Bektas, Yasin; Yucel, Ceyhan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
The large-scale migrations towards large cities that occurred in Turkey after the 1950s have brought about many spatial and social problems. The massive migrant populations moving from rural areas to cities cannot be integrated with the city completely due to these problems. These groups, which settle in the city through informal channels, differentiate in social and economic dimension throughout the city in the course of time. Urban problems caused by the settlement pattern of the large-scale migration in large cities, socio-economic differences and the change of migration quality constitute the spatial divergence. The scarcity of sources in cities and applications performed by upper local institutions on the formal section of the city have created urban inequality throughout the city and accelerated the divergence even further. This study aims to focus on divergences, which occur as a result of the migration movements and are caused by social, economic and spatial inequalities on the area of Ankara-Altindag Hill Squatter Region. Within the scope of this objective, we examined the spatial segregation as both a physical and a social issue using quantitative and qualitative data. The spatial segregation in Eski Altindag was followed profoundly in two stages as local plane and supra-local plane, with the help of interviews.
Keywords: Squatter; migration; spatial segregation; Architecture